Public transit performance: what does one learn from frontier studies? - Bruno De Borger (2002)
This paper provides a comprehensive survey of the literature on production and cost frontiers for public transit operators, and it evaluates the contributions of frontier analysis to the understanding of the performance of the public transport sector. The authors first succinctly contrast best practice (or frontier) and average practice specifications of technology. They also review relevant performance indicators and the methods to measure them. Next, the existing frontier studies measuring urban transit performance are systematically summarized and critically assessed. It is shown that the organization of the market, contract design, the degree and nature of the regulatory regime, and the characteristics of the network being served are all important determinants of inefficiency. However, although the frontier literature has substantially contributed to the knowledge of urban transit technologies and the determinants of performance, it is found that many important issues remain unresolved.